Self Expanding Metallic Stent Placement as a Palliative Therapy for an Advanced Gastric Cancer Patient - Rabbinu Rangga Pribadi; Gerie Amarendra; Marcellus Simadibrata; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Patients with gastric cancer which infiltrates distal esophagus often complain of dysphagia. Stenting is currently the therapy of choice for malignant dysphagia. Self expanding metallic stent (SEMS) placement has become the standard stenting therapy.We reported a case of 63 year old male patient with an advanced gastric adenocarcinoma which infiltrated distal esophagus who complained of dysphagia. The diagnosis was made based on esophago gastro duodenoscopy (EGD), histopathology study and contrast enhanced abdominal computed tomography (CT) scan. Patient underwent esophageal stenting successfully. This case report demonstrates SEMS placement as an effectivepalliation therapy in patient with an advanced gastric cancer which infiltrated distal esophagus.Keywords: gastric cancer, self expanding metallic stents, malignant dysphagia